ETNOGRAFI 5 PEREMPUAN PENYAPU JALAN (Study Kasus di Kecamatan Pontianak Tenggara Kota Pontianak Kalimantan Barat) - LYUDMITA KAROLINA MARITO BAKARA (Balale' : Jurnal Antropologi, 2021)
AbstractThe street sweeper profession is always described as a world of work for men. The street sweeper workers have a high risk. Currently the street sweeper profession is not only done by men, but also women. Women as street sweepers can be found in almost all parts of Indonesia. The Street Sweeper is a natural and common thing. The research is a case study which focuses on 5 street sweeper women in Kecamatan Pontianak Tenggara, Kota Pontianak, Kalimantan Barat. Working as a street sweeper is a source of income that can help the household economy to fulfil primary, secondary and tertiary needs. The formulation of the research problem is "How is the life of the street sweepers women in Kecamatan Pontianak Tenggara, Kota Pontianak, Kalimantan Barat". The purpose of this research is to describe and analyze the background of the 5 street sweeper women. describe and analyze the Public and Domestic sectors of the 5 street sweeper women and the work equipment that was used. This study uses qualitative ethnographic methods, interviews and observations and uses Domain data analysis techniques using functionalism theory. These methods and theories were chosen in order to obtain more accurate and descriptive research data about the Ethnography of 5 Street Sweeper Women, the data stated in a reasonable condition or as they are in accordance with the results of research in the field that are in-depth and comprehensive regarding the issues raised. Keywords: Street Sweeper, Women, Public and Domestic AbstrakProfesi Penyapu Jalan selalu digambarkan sebagai dunia pekerjaan untuk laki-laki. Pekerja Penyapu Jalan memiliki resiko yang tinggi. Saat ini profesi penyapu jalan tidak hanya dilakukan oleh laki-laki, namun juga perempuan. Perempuan sebagai Penyapu Jalan dapat ditemukan dihampir seluruh wilayah Indonesia. Perempuan Penyapu Jalan menjadi hal wajar dan lumrah. Studi kasus dalam penelitian berfokus pada 5 perempuan Penyapu Jalan di Kecamatan Pontianak Tenggara, Kabupaten Kota Pontianak, Kalimantan Barat. Bekerja sebagai Penyapu Jalan adalah sumber penghasilan yang dapat membantu perekonomian rumah tangga untuk memenuhi kebutuhan primer, sekunder dan tersier. Rumusan masalah penelitian yaitu “Bagaimana kehidupan perempuan penyapu jalan di Kecamatan Pontianak Tenggara”. Tujuan penelitian adalah mendeskripsikan dan menganalisis latar belakang kehidupan 5 perempuan Penyapu Jalan, mendeskripsikan dan menganalisis sektor Publik dan Domestik pada 5 perempuan Penyapu Jalan serta perlengkapan kerja yang digunakan. Penelitian ini menggunakan metode Etnografi yang bersifat kualitatif, wawancara dan observasi serta menggunakan teknik analisis data Domain dengan menggunakan teori fungsionalisme. Metode dan teori ini dipilih agar mendapatkan data penelitian yang lebih akurat dan bersifat memaparkan tentang Etnografi 5 Perempuan Penyapu Jalan, data yang dinyatakan dalam keadaan sewajarnya atau apa adanya sesuai dengan hasil penelitian di lapangan yang bersifat mendalam dan menyeluruh mengenai masalah yang diangkat. Kata Kunci: Penyapu Jalan; Perempuan; Publik dan Domestik